Trauma, resiliency, and risk perception of flash flood children survivors in Barangay Tigum, Pavia. - Lentija, Zyra F. (2009.)
The study sought to describe and determine the extent of disaster trauma, resiliency level and risk perception of children survivors towards flash flood. They displayed a high resiliency level indicating that they are able to cope and treat life's stresses optimistically. Predominantly, they developed a low risk perception or a positive one rather than a heightened or negative risk perception.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo.
Keywords: Disaster trauma on flash flood